2005
DOI: 10.2174/1381612053507648
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Following Photodynamic Tumor Therapy: Induction, Mechanisms and Detection

Abstract: As a treatment modality for malign and certain non-malignant diseases, photodynamic therapy (PDT) involves a two step protocol which consists of the (selective) uptake and accumulation of a photosensitizing agent in target cells and the subsequent irradiation with light in the visible range. Reactive oxygen species (ROS) produced during this process cause cellular damage and, depending on the treatment dose/severity of damage, lead to either cellular repair/survival, apoptotic cell death or necrosis. PDT-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 195 publications
(200 reference statements)
1
69
0
2
Order By: Relevance
“…The balance between apoptosis and necrosis after PDT in vitro depends on several parameters, including the total PDT dose (PDT dose is the product of PS concentration and light fluence), the intracellular localization of the PS, the fluence rate, the oxygen concentration and the cell type 4 . There is an extensive body of literature that examines the pathways of apoptosis that are induced after PDT in both normal and tumour cells in tissue culture, such as signalling pathways 30,31 , mitochondrial events 4 and mediators of apoptosis 32 . The occurrence of apoptosis after PDT in tumours in vivo has also been shown [33][34][35] , but there have been no studies looking at in vivo clearance mechanisms of apoptotic cells in tumours after PDT.…”
Section: Effects Of Pdt On Tumour Cellsmentioning
confidence: 99%
“…The balance between apoptosis and necrosis after PDT in vitro depends on several parameters, including the total PDT dose (PDT dose is the product of PS concentration and light fluence), the intracellular localization of the PS, the fluence rate, the oxygen concentration and the cell type 4 . There is an extensive body of literature that examines the pathways of apoptosis that are induced after PDT in both normal and tumour cells in tissue culture, such as signalling pathways 30,31 , mitochondrial events 4 and mediators of apoptosis 32 . The occurrence of apoptosis after PDT in tumours in vivo has also been shown [33][34][35] , but there have been no studies looking at in vivo clearance mechanisms of apoptotic cells in tumours after PDT.…”
Section: Effects Of Pdt On Tumour Cellsmentioning
confidence: 99%
“…After 4 and 12 h, PSs were localised in the plasma membrane and in peripheral regions of the cytoplasm, and more necrotic cells in comparison to apoptotic were observed after longer time periods, and especially when a higher light dose was used (Kramer-Marek et al 2006). Conversely, targeting mitochondria in PDT is preferable to targeting plasma membrane and lysosomes, because it was shown to induce apoptosis rapidly, both in vivo and in vitro (Morgan and Oseroff 2001;Almeida et al 2004;Plaetzer et al 2005;Bonneau and Vever-Bizet 2008).…”
Section: Lipophilicity and Cellular Uptakementioning
confidence: 99%
“…PDT causes tumour damage directly by inducing necrosis, apoptosis (Dougherty et al 1998, Kessel & Luo 1998, Plaetzer et al 2005 or autophagy (Kessel et al 2006, Buytaert et al 2006 in the tumour cells. PDT may also stiumulate shutdown of the tumour vasculature (Fingar et al 1999, Engbrecht et al 1999, Chen et al 2002, Woodhams et al 2006 and, in addition, PDT is shown preclinically to activate antitumour immunity (Castano et al 2006, Kousis et al 2007.…”
Section: Pdt Mediated Targeting Of Tumoursmentioning
confidence: 99%